2022
DOI: 10.15537/smj.2022.43.2.20210433
|View full text |Cite
|
Sign up to set email alerts
|

Demographic features, clinical characteristics, and prognostic factors of non-epithelial ovarian tumors at Princess Noorah Oncology Center, National Guard Hospital, Jeddah, Saudi Arabia

Abstract: Objectives: To reveal the demographic features, prognostic factors, and tumor characteristics of patients with non-epithelial ovarian tumors (NEOTs). Methods:This cross-sectional study was performed using data from all female patients diagnosed with NEOT (germ cell [GC], sex cord-stromal cells [SCSC], sarcoma, and small cell carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…However, the probability of survival of MOGCTs and SCSTs varies noticeably between studies, and there are only a small number of previous investigations that have looked at the time course of survival of these cancers, as well as the influence of stage at diagnosis [3,8,9]. Consistent with our findings, several researchers have suggested that patients with SCSTs have a poor survival rate when compared with MOGCTs [1,3,10]. In our research, PSM was used to adjust the confounders, increasing the robustness of the results [11].…”
Section: Discussionsupporting
confidence: 88%
“…However, the probability of survival of MOGCTs and SCSTs varies noticeably between studies, and there are only a small number of previous investigations that have looked at the time course of survival of these cancers, as well as the influence of stage at diagnosis [3,8,9]. Consistent with our findings, several researchers have suggested that patients with SCSTs have a poor survival rate when compared with MOGCTs [1,3,10]. In our research, PSM was used to adjust the confounders, increasing the robustness of the results [11].…”
Section: Discussionsupporting
confidence: 88%
“…Another study also indicated that complete surgical cytoreduction had the best survival benefit in advanced epithelial ovarian cancer patients ( 34 ). Balkhy et al indicated that surgery was the cornerstone of treatment for most stages of non-epithelial ovarian cancers, which might correlate with the prognosis of those patients ( 35 ). A retrospective review showed that ovarian cancer patients receiving intraperitoneal chemotherapy were associated with improved 10-year survival of these patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%